Peranan Visum et Repertum Bagi Korban Tindak Pidana Pembunuhan - Tania Putri Nurtianti; Indra Yudha Koswara (Peneliti.net, 2023)
A medical examination of human individuals, whether they live or die, or only a portion of their bodies, conducted by forensic doctors at the official request of investigators for the benefit of the court, is known as visum et repertum. It plays an important role in revealing the material truth in the case of murder, wherein visum et repertum can expose the results of the examination of the body of the murder victim to reveal the facts regarding how the victim died and the way the perpetrator killed the victim. For victims of homicide crimes, visum et repertum is a legal doctrine that can be applied to murder victims to represent them in court. So that visum et repertum as evidence in the criminal process of murder is a must because the process of examining the victim's body cannot be prevented. Any person who obstructs the examination of the victim's body is considered to have hindered the investigation process and is subject to punishment in accordance with Article 222 of the Criminal Code (KUHP).